Furfuryl Alcohol Treatment of Bamboo Betung (Dendrocalamus asper Backer ex K. Heyne) Strips - Krisdianto Krisdianto; Peter Vinden; Simon Prezwloka (Wood Research Journal, 2019)
Based upon  successful chemical modification of  wood, bamboo strips  were subjected to  furfurylation treatment. Furfurylation in the mean of impregnating furfuryl alcohol to the bamboo and then heated at 100°C for 24 hours to produce solid polymeric resin. The success of furfurylation is assessed by uptake and the weight percentage gain of furfurylated bamboo strips. However, the treatability of dry bamboo strip is relatively poor. This paper studies the furfurylation process of bamboo betung (Dendrocalamus asper Backer ex K.Heyne) strips by soaking, vacuuming and the combinations thereof. Results showed that soaking bamboo strips for two days after vacuum treatment achieved optimum uptake of furfuryl alcohol solutions and gave rise to an 80% weight gain. Catalyst addition during furfurylation did not increase the weight percent gain. Water was an active solvent carrier for achieving higher weight gains